Systemic Bone Density at Disease Onset Is Associated With Joint Erosion Progression in Early Naive to Treatment Rheumatoid Arthritis: A Prospective 12-Month Follow-Up Open-Label Study - Bruno, Dario; Fedele, Anna Laura; Tolusso, Barbara; Barini, Angelina; Petricca, Luca; Di Mario, Clara; Barini, Antonella; Mirone, Luisa; Ferraccioli, Gianfranco; Alivernini, Stefano; Gremese, Elisa (Frontiers in Medicine, 2021)
Objectives: Osteoporosis and bone erosions are hallmarks of Rheumatoid Arthritis (RA) since disease onset underpinned by the inflammatory burden. In this observational study we aimed to dissect the putative RA-related parameters and bone-derived biomarkers associated with systemic and focal bone loss at disease onset and with their progression. Methods: One-hundred and twenty-eight patients with early Rheumatoid Arthritis (ERA) were recruited at disease onset. At study entry, demographic, clinical and immunological parameters were recorded. Each ERA patient underwent plain X-rays of hands and feet at study entry and after 12 months to assess the presence of erosions. After enrollment, each patient was treated according to the recommendations for RA management and followed based on Treat to Target (T2T) strategy. At baseline, blood samples for soluble biomarkers were collected from each patient and plasma levels of Osteoprotegerin (OPG), Receptor Activator of Nuclear Factor κB ligand (RANKL), Dickkopf-1 (DKK1) and Interleukin 6 (IL-6) were assessed by Enzyme-Linked ImmunoSorbent Assay (ELISA). Seventy-one ERA patients underwent bone mineral density (BMD) measurement at the left femoral neck and second to fourth lumbar spine vertebrae (L2-L4) by Dual-energy X-ray absorptiometry (DXA). Results: Among the whole cohort, 34(26.6%) ERA patients with bone erosions at study entry had a higher disease activity (p=0.02) and IL-6 plasma levels (p=0.03) than non-erosive ones. Moreover, at DXA, 33(46.5%) ERA patients had osteopenia and 16(22.5%) had osteoporosis and patients with baseline bone erosions were more likely osteopenic/osteoporotic than non erosive ones (p=0.03), regardless of OPG, RANKL and DKK1 plasma levels. Obese ERA patients were less likely osteopenic/osteoporotic than normal weigh ones (p=0.002), while anti-citrullinated protein antibodies (ACPA) positive ERA patients were more likely osteopenic/osteoporotic than ACPA negative ones (p=0.034). At logistic regression analysis, baseline Disease Activity Score measured on 44 joints (DAS44) [OR:2.46(1.11-5.44)] and osteopenic/osteoporosis status[OR:7.13(1.27-39.94)] arose as independent factors of erosiveness. Baseline osteopenic/osteoporotic status and ACPA positivity were associated with bone damage progression during the follow-up. Conclusions: Bone erosions presence associates with systemic bone loss since the earliest phases of RA, suggesting that the inflammatory and autoimmune burden, underpinning RA, represent crucial enhancers of bone remodeling either locally as at systemic level.